Intestinal inflammation disrupts energy metabolism in layer pullets: insights into energy partitioning and intestinal metabolomic profiling - Qiuyu Jiang; Bingjian Huang; Simiao Chen; Lihua Zhao; Zhibin Ban; Bingkun Zhang (Journal of Animal Science and Biotechnology)
Abstract Background Intestinal inflammation is an energy-consuming process that may alter energy supply and demand in poultry. During inflammation, the intestinal energy metabolic profile and the patterns of energy partitioning remain unclear. This study investigated the effects of intestinal inflammation on energy intake, heat production (HP), retained energy (RE) and intestinal energy metabolites in layer pullets. Methods After 7 d dietary adaption, 32 “Jing Tint 6” layer pullets with average body weight (1,123.50 ± 8.55 g) were selected from 96 birds, and randomly assigned to two groups (CON: Control group, INFL: Inflammation group) with 8 replicates per group. Indirect calorimetry analysis was conducted over 7 d to determine HP and fasting HP (FHP). During this period, pullets in INFL group received 4 mL/d of 0.6 g/mL dextran sulfate sodium (DSS) via oral gavage to induce intestinal inflammation. After the calorimetry, intestinal tissues were collected post-euthanasia from one bird per replicate for morphological and mucosal metabolomic analysis. Results Birds exhibited significantly lower apparent metabolizable energy (AME) intake (P < 0.001) during intestinal inflammation, accompanied by compromised RE and RE as fat (P < 0.001), suggesting that birds consumed body energy to sustain energy demands. Targeted metabolomic studies identified 11 energy metabolites differentially expressed in ileal mucosa between CON and INFL groups. Specifically, DSS induction significantly increased (P < 0.05) adenosine triphosphate (ATP) level and reduced (P < 0.001) nicotinamide adenine dinucleotide (NAD+) level in ileal mucosa of pullets. In parallel, metabolic adaptations such as enhanced glycolytic intermediates, reduced amino acids, α-ketoglutarate (α-KG) accumulation and suppressed expression of genes encoding enzymes involved in tricarboxylic acid (TCA) cycle were observed in the inflamed ileum of pullets. Conclusion Immune stimulation by DSS induced a negative energy balance in layer pullets, characterized by reduced AME intake (−190.47 kJ/kg BW0.75) and compromised RE (−18.81% of AME intake). Disruption of intestinal energy profiling was observed in inflammation-challenged pullets, such as accumulation of α-KG and ATP, reduced NAD+ and amino acids, which could provide valuable insights for developing effective intervention strategies.